2014
DOI: 10.14712/18059694.2014.40
|View full text |Cite
|
Sign up to set email alerts
|

The Vegf and BMP-2 Levels in Patients With Ankylosing Spondylitis and the Relationship to Treatment With Tumour Necrosis Factor Alpha Inhibitors

Abstract: Summary:Introduction: Ankylosing spondylitis (AS) is an inflammatory rheumatic disease characterized by the development of osteoproductive changes in the spine which could possibly result in ankylosis. Treatment with tumour necrosis factor alpha (TNFα) inhibitors has proved to be an important step forward in the treatment of this disease, but for the time being it is not clear whether it favourably influences radiographic progression of the disease. Vascular endothelial growth factor most probably plays a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Serum VEGF was also lower in users of TNF-blockers compared with non-users. The finding is in accordance with the previous studies by Tošovský et al [ 43 ] and Pedersen et al [ 44 ] who also reported that AS patients treated with TNF inhibitors had lower serum VEGF compared to untreated patients. The association between VEGF and BMD has not previously been found in AS patients.…”
Section: Discussionsupporting
confidence: 93%
“…Serum VEGF was also lower in users of TNF-blockers compared with non-users. The finding is in accordance with the previous studies by Tošovský et al [ 43 ] and Pedersen et al [ 44 ] who also reported that AS patients treated with TNF inhibitors had lower serum VEGF compared to untreated patients. The association between VEGF and BMD has not previously been found in AS patients.…”
Section: Discussionsupporting
confidence: 93%
“…TNFα inhibitors are the biologic agents that are indicated frequently in AS. VEGF levels also significantly decrease following anti-TNFα therapy [91,98,99]. VEGF also correlates with bone mineral density in AS treatment with infliximab [99].…”
Section: Vegf In Asmentioning
confidence: 97%
“…The exact origin of the BMP2 detected in the L-PRF is difficult to point out, as BMP2 is a molecule specific to bone cells; the ELISA kit itself was designed mostly for bone tissue extracts and bone cell culture supernatants. Small quantities of BMP2 can be detected in the blood in some conditions [36], but its overexpression in blood is often associated with various pathologies [37,38]. As BMP2 is not supposed to be released by platelets, consequently the different cell populations (mostly leukocytes) living in the L-PRF clot released BMP2.…”
Section: Different Protocol Different Prf Different Growth Factors mentioning
confidence: 99%